2014
DOI: 10.1186/1471-2164-15-331
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome positioning and histone modifications define relationships between regulatory elements and nearby gene expression in breast epithelial cells

Abstract: BackgroundThe precise nature of how cell type specific chromatin structures at enhancer sites affect gene expression is largely unknown. Here we identified cell type specific enhancers coupled with gene expression in two different types of breast epithelial cells, HMEC (normal breast epithelial cells) and MDAMB231 (triple negative breast cancer cell line).ResultsEnhancers were defined by modified neighboring histones [using chromatin immunoprecipitation followed by sequencing (ChIP-seq)] and nucleosome depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 85 publications
(108 reference statements)
1
46
0
Order By: Relevance
“…Because recent studies have shown that a nucleosome-depleted region (NDR) flanked on each side by a nucleosome having the active enhancer histone mark H3K27Ac is where TFs actually bind [5, 13], we used public and newly generated Nucleosome Occupancy and Methylome Sequencing (NOMe-seq), DNaseI-seq, and FAIRE-seq datasets to further narrow enhancer regions (see Additional file 1: Supplementary Methods for a detailed description of the creation of the enhancer file and Additional file 2: Table S1 for a list of datasets). These narrowed regions represent the functional (TF binding) compartment of the larger regions defined by ChIP-seq data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because recent studies have shown that a nucleosome-depleted region (NDR) flanked on each side by a nucleosome having the active enhancer histone mark H3K27Ac is where TFs actually bind [5, 13], we used public and newly generated Nucleosome Occupancy and Methylome Sequencing (NOMe-seq), DNaseI-seq, and FAIRE-seq datasets to further narrow enhancer regions (see Additional file 1: Supplementary Methods for a detailed description of the creation of the enhancer file and Additional file 2: Table S1 for a list of datasets). These narrowed regions represent the functional (TF binding) compartment of the larger regions defined by ChIP-seq data.…”
Section: Resultsmentioning
confidence: 99%
“…In C42B, RWPE1, MCF7, and MCF10A cells, H3K27Ac ChIP assays were performed using H3K27Ac antibody (Cat # 39133 Lot # 21311004, Active Motif, Carlsbad, CA, USA or ab4729 Abcam, Cambridge, MA, USA), as previously described [5, 35]. Each ChIP-seq experiment was performed in duplicate, and ChIP-seq libraries were sequenced on either Illumina Hiseq 2000 or Nextseq 500 machines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike enhancers, which are located far from a TSS, are cell-type specific, and are closely linked to cellular identity (Rhie et al 2014(Rhie et al , 2016, promoter elements are crucial for basal transcription of genes. The majority of human promoters are classified as CpG island promoters; these promoters are generally active in most cell types (Deaton and Bird 2011).…”
Section: How Does Zfx Regulate Transcription Of Cpg Island Promoters mentioning
confidence: 99%
“…The eventual outcome of different methyl marks not only depends on the modified residue itself, but also on the context of other posttranslational histone modifications on the same and neighboring nucleosomes (histone code) (15,16). To add a layer of complexity, recent research indicates that histone methylation may function in regulating gene expression by affecting nucleosome positioning (17,18). Furthermore, histone methylation is important for X inactivation, cell fate determination, and terminal differentiation (19,20).…”
Section: Histone Methyltransferasesmentioning
confidence: 98%